2015
DOI: 10.5038/2375-0901.18.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing and Assessing the Experience of Traveling by Public Transport

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…As will be elaborated upon later, there are also efforts to further develop or refine existing techniques from development banks, cooperative research organizations and NGOs. The literature also elaborates on the appraisal of user experiences and quality of service (Phillips and Guttenplan, 2003;Hawas et al, 2012;Olivková, 2015;Schiefelbusch, 2015;Godavarthy et al, 2015), the assessment of routes and networks (i.e. Banai, 2006), as well as the appraisal of maintenance investment (i.e.…”
Section: Assessment Methods From Around the World Potentially Useful mentioning
confidence: 99%
“…As will be elaborated upon later, there are also efforts to further develop or refine existing techniques from development banks, cooperative research organizations and NGOs. The literature also elaborates on the appraisal of user experiences and quality of service (Phillips and Guttenplan, 2003;Hawas et al, 2012;Olivková, 2015;Schiefelbusch, 2015;Godavarthy et al, 2015), the assessment of routes and networks (i.e. Banai, 2006), as well as the appraisal of maintenance investment (i.e.…”
Section: Assessment Methods From Around the World Potentially Useful mentioning
confidence: 99%
“…Also, (Aydin et al, 2015) identified welcoming as one of the most important attributes in evaluating customer satisfaction in rail transit service. (Redman et al, 2013), (Jain et al, 2014), (Keyvan-Ekbatani & Vaziri, 2012), (Güner, 2018), (Boujelbene & Derbel, 2015), (Barbosa et al, 2017), (Celik et al, 2013), (Calvo & Ferrer, 2018), (Nguyen-Phuoc, Su, Tran, Le, & Johnson, 2020), (Pedroso, Bermann, & Sanches-Pereira, 2018), (Camargo Pérez, Carrillo, & Montoya-Torres, 2014), (Eboli & Mazzulla, 2011), (Nassereddine & Eskandari, 2017), (J. de Oña, de Oña, & López, 2016), (Aydin et al, 2015), (Carreira et al, 2013) Comfort (Chou et al, 2014), (R. De Oña et al, 2014), (Zhang et al, 2019), (dell'Olio et al, 2011, (Nathanail, 2008), (Schiefelbusch, 2015), (Keyvan-Ekbatani & Vaziri, 2012), (Lee, 2018), (Pedroso et al, 2018), (Eboli & Mazzulla, 2015), (Mahmoud & Hine, 2016), (Barbosa et al, 2017), (Celik et al 2013), (Güner, 2018), (Redman et al, 2013), (Eboli & Mazzulla, 2011), (J. de Oña et al, 2016, (Aydin et al, 2015), (Sam et al 2018), (Carreira et al, 2013) Frequency (Redman et al, 2013), (Jain et al, 2014),…”
Section: Welcomingmentioning
confidence: 99%
“…There are a few cases in which experience was not sufficient. It was used only in the analysis before planning procedures which is insufficient and should be used in all stages of transport planning [17]. Given that integration is a demanding task which depends on a range of elements that determine passenger behaviour, every change may cause non-sustainability of an element in the integration.…”
Section: Role Of Integrated Passenger Transportmentioning
confidence: 99%